2002
DOI: 10.1177/153537020222700408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polyamines on the Release of Gonadotropin-Releasing Hormone and Gonadotropins in Developing Female Rats

Abstract: Polyamines, putrescine (PUT), spermidine (SPD), spermine (SPM), and agmatine (AGM), are polycationic amines related to multiple cell functions found in high concentrations during the development of hypothalamus and pituitary. In previous works, we demonstrated that α-difluoromethylornithine (DFMO), an inhibitor of polyamines biosynthesis, induced a delay in puberty of female rats, accompanied by high, sustained follicle-stimulating hormone (FSH) levels during the infantile period. Also, DFMO treatment induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…A study identified polyamine as a regulator of GnRH‐I in 6‐ and 15‐day‐old female rats (Thyssen, Hockl, Chamson, Lux‐Lantos, & Carlos, 2002). This study further described through ex vivo approach that polyamine treatment to the hypothalamic and anterior pituitary tissue obtained from the 6‐ and 15‐ days old rats, regulated the secretion of GnRH‐I, FSH, and LH (Thyssen et al, 2002). Our group recently showed that polyamines and their associated factors had a positive correlation with the expression pattern of GnRH‐I in the medial preoptic area (MPA) during the estrous cycle of female rats (Fernandes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study identified polyamine as a regulator of GnRH‐I in 6‐ and 15‐day‐old female rats (Thyssen, Hockl, Chamson, Lux‐Lantos, & Carlos, 2002). This study further described through ex vivo approach that polyamine treatment to the hypothalamic and anterior pituitary tissue obtained from the 6‐ and 15‐ days old rats, regulated the secretion of GnRH‐I, FSH, and LH (Thyssen et al, 2002). Our group recently showed that polyamines and their associated factors had a positive correlation with the expression pattern of GnRH‐I in the medial preoptic area (MPA) during the estrous cycle of female rats (Fernandes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report that shows that low dose putrescine treatment significantly (*** p < .001) increased the serum GnRH‐I levels, further increasing the serum gonadotropin levels. Thyssen et al (2002) previously showed that polyamines regulate FSH and LH using 6‐ and 15‐day‐old pituitary of female rats. Previous studies have shown that GnIH suppresses gonadotropin release by inhibiting GnRH‐I release (46,58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver levels of polyamines (putrescine, spermidine, and spermine) present in acid-extracts from cytosol were measured as benzoyl derivatives using HPLC (Beckman-Golden system HPLC with UV detector), prepared essentially as described by Thyssen et al [29]. The equipment used was a Beckman-Golden system HPLC with UV detector, and a C-18 reverse column was employed.…”
Section: Methodsmentioning
confidence: 99%
“…GnRH concentration in culture media was determined as previously described (Thyssen et al, 2002). Briefly, samples were analyzed in duplicate using the anti GnRH antiserum (R1245 antiGnRH-BSA, final dilution 1 : 50,000) kindly provided by Dr Nett, GnRH was iodinated with 125 I (NEZ 03 3 H, DuPont NEN Life Sciences Products, Inc, Boston, MA) by the chloramin-T method.…”
Section: Ria For Gnrhmentioning
confidence: 99%